The functionality of the historical and cultural context in the theme ground of the Jacek Bochenski’s novel «Naso the Poet» - Давиденко, Іван Олександрович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The present paper concentrates on analyzing the peculiarities of the life theme reading. «Naso the Poet» («Nazo poeta», 1969) by Jacek Bochenski is considered in our study as a phenomenon of Polish modernist literature. Though the narrative of the novel actually added up to the interpretation of the events in the great Roman poet’s life, Bochenski dispensed without the representation principle that was generally accepted in the 19th century. Instead of it, dramatization became the dominant stylistic device in his novel. It is shown that the main theme of the Polish author’s novel is searching of the real cause of the poet’s exile.